Nenehno izboljševanje tlačnega litja s postopkom Šest sigem - Pavletić, Duško (Strojniški vestnik, 2007)
This paper deals with the application of a Six Sigma methodology to the continuous improvement of an aluminium die-casting process. A Six Sigma improvement project was initiated in an aluminium die-casting process, with the aim to reduce the amount of machining scrap from an average of 4.12% to less than 2%, and the amount of material scrap from 11.43% to an average of less than 4%. The parameters with a major influence on the level of scrap were defined in a cause-and-effect diagram, analyzed, improved where necessary,and put under control using Six Sigma tools and methods. Although the initial project goals were not completely met, major die-casting process improvements were made, resulting in significant savings.
Keywords: tlačno litje; šest sigm; aluminij; aluminum; izboljšave